Percutaneous Cryoablation of Renal Tumors: Initial Indian Experience - Ujjwal Gorsi; Rishabh Jain; Akash Bansal; Naveen Kalra; Mandeep Kang; Sreedhara B. Chaluvashetty; Ravimohan Suryanarayan Mavuduru; Santosh Kumar; Shrawan K. Singh; Manavjit Singh Sandhu (Journal of Clinical Interventional Radiology ISVIR)
Purpose The purpose of this study was to report short-term outcomes of cryoablation of early-stage renal tumors (T1a and T1b) at a tertiary hospital in India. Methods This was a retrospective study of consecutive patients who underwent cryoablation for renal cell carcinoma (RCC) from November 2018 to June 2020. Cryoablation was performed under combined ultrasound and computed tomography guidance using a helium-argon cryoablation system. Tumor number, size, location, nephrometry score, relationship of the tumor with pelvicalyceal system, and adjacent organs were tabulated, and technical and clinical success evaluated. Early and late recurrence and complications were also assessed. Results Eleven patients (median age: 62 years) with 11 tumors underwent cryoablation. The mean tumor size was 2.58 cm (range: 1.62–5.62 cm) with 10 lesions being T1a and one lesion T1b. Tissue sampling was done in 9/11 patients, 3 were papillary RCC and the rest, clear cell RCC. In two patients, the tumor was completely endophytic, three patients had partially endophytic tumors while 6 patients had exophytic lesions. The median nephrometry score was 6 (range: 4–11, Mode 4). Technical success was achieved in all patients. Complete response was achieved in 81% (9/11) of the patients at 1-month follow-up. Median follow-up period was 6 months. Two patients showed residual disease on follow-up imaging at 1 and 3 months, respectively. Conclusion Cryoablation is a promising, relatively new minimally invasive therapy for treating small renal tumors in India. It is safe, technically feasible, and shows excellent short-term efficacy.